2020
DOI: 10.21608/jabps.2020.21160.1064
|View full text |Cite
|
Sign up to set email alerts
|

Novel Benzimidazole/Hydrazone Derivatives as Promising Anticancer Lead Compounds: Design, Synthesis, and Molecular Docking Study

Abstract: A novel series of benzimidazole-hydrazone derivatives was designed and synthesized as a potential anti-cancer agents. The structure of the target compounds was assured using different spectroscopic methods such as IR, 1 H NMR, 13 C NMR and elemental analysis. These new compounds were examined and evaluated for their antiproliferative activities against 60 different cell lines. Combination of benzimidazole scaffold with hydrazone group exhibited promising anti-cancer activity. Compounds 3a and 3b showed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The IC50 values ( Table 4 ) for HCT-116 were 29.5 + 4.53 µM, 57.9 + 7.01 µM, 40.6 + 5.42 µM for 6a , 6b and 6c , respectively. These results indicate a high capacity of these compounds to inhibit HCT-116 growth when compared, for example, to novel benzimidazole derivatives synthesized by Morcoss et al, which inhibited the proliferation of HCT-116 by approximately 56% at a concentration of 10 mM [ 1 ]. Furthermore, some novel pyrazole-benzimidazole derivatives synthesized by Ren et al have demonstrated significant antiproliferative activity against HCT-116 cells with the IC50 values of 4.33, 5.15 and 4.84 μM [ 65 ].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The IC50 values ( Table 4 ) for HCT-116 were 29.5 + 4.53 µM, 57.9 + 7.01 µM, 40.6 + 5.42 µM for 6a , 6b and 6c , respectively. These results indicate a high capacity of these compounds to inhibit HCT-116 growth when compared, for example, to novel benzimidazole derivatives synthesized by Morcoss et al, which inhibited the proliferation of HCT-116 by approximately 56% at a concentration of 10 mM [ 1 ]. Furthermore, some novel pyrazole-benzimidazole derivatives synthesized by Ren et al have demonstrated significant antiproliferative activity against HCT-116 cells with the IC50 values of 4.33, 5.15 and 4.84 μM [ 65 ].…”
Section: Resultsmentioning
confidence: 89%
“…Cancer is one of the world’s biggest medical challenges [ 1 ]. Cancer is characterized by cell cycle disruption, which inhibits cell differentiation and promotes uncontrollable cell growth [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Target compounds 3a – o were chemically synthesized as shown in Scheme 1 . Compounds 1a , b were prepared according to the reported methods [ 27 ]. The chemical structures of such compounds were proven by matching their spectral data with the reported data [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1a , b were prepared according to the reported methods [ 27 ]. The chemical structures of such compounds were proven by matching their spectral data with the reported data [ 27 ]. The key intermediates compounds, benzimidazole-hydrazone 2a , b , were prepared by heating compounds 1a , b with hydrazine hydrate at reflux temperature for 12 h. The final target benzimidazole–Shiff hybrids 3a – o were prepared by reaction of the benzimidazole hydrazone derivatives 2a , b with the appropriate acetophenone or aldehyde derivatives in ethanol in the presence of few drops of acetic acid as catalyst under reflux conditions.…”
Section: Resultsmentioning
confidence: 99%
“…N-acylhydrazones are featured by (CO-NH-N=CH) moiety, which when connected to heterocyclic scaffold, very often leads to compounds with interesting biological activities, including anticancer, [1,2] antibacterial, [3][4][5] antiviral, [6,7] and antihypertensive [8] properties. The molecules based on imidazo [1,2-a]pyridine are heterobicyclic compounds that also exhibited antimicrobial [9][10][11] antiinflammatory, [12] anticancer, [13,14] and antiparasitic [15] properties, among many others.…”
Section: Introductionmentioning
confidence: 99%